Hepcidin Is a Reliable Marker of Iron Deficiency Anemia in Newly Diagnosed Patients with Inflammatory Bowel Disease. (28th November 2020) - Stojkovic Lalosevic, Milica; Toncev, Ljubisa; Stankovic, Sanja; Dragasevic, Sanja; Stojkovic, Stefan; Jovicic, Ivana; Stulic, Milos; Culafic, Djordje; Milovanovic, Tamara; Stojanovic, Marija; Aleksic, Marko; Stjepanovic, Mihailo; et al.
Abstract : Background and Aim . Differentiating iron deficiency anemia (IDA) from anemia of chronic disease (ACD) in patients with inflammatory bowel disease (IBD) represents a clinical challenge. Hepcidin is a polypeptide synthetized in the liver, and iron levels or inflammation mostly regulate hepcidin production. Our aim was to determine serum hepcidin levels in patients with inflammatory bowel disease (IBD) as well to investigate whether hepcidin levels correlate with disease activity. Material and Methods . A case-control study was preformed among newly diagnosed IBD patients and same number age- and sex-matched healthy controls. All patients underwent a total ileocolonoscopy. Complete blood count was obtained in addition to inflammatory markers (CRP, erythrocyte sedimentation rate-ESR). Serum levels of hepcidin were determined with commercially available enzyme-linked immunosorbent assay (DRG Instruments Marburg, Germany). Serum iron, TIBC, and UIBC were assessed with an electrochemiluminesence immunoassay, and soluble transferrin receptor (sTfR) was assessed using an immunoturbidimetric method. Mayo score and CDAI, respectively, were calculated for each patient. Statistical analyses were performed using the SPSS software version 20.0 for Windows. Results . There was a high statistically significant difference between IBD patients and controls in levels of hepcidin (P < 0.01 ). Namely, serum hepcidin levels were significantly higher in the control group. There was no statistically significant correlation of serum hepcidin with CRP, Mayo score, or CDAI, respectively (P > 0.05 ). However, we have found a statistically significant negative correlation of sTfR and TIBC with hepcidin (P < 0.01 ). Conclusion . Results of our study suggest that hepcidin is a reliable marker of IDA in patients with IBD, and it could be used in routine clinical practice when determining adequate therapy in these patients.